Predictors of adequate physical activity within a multiethnic polycystic ovary syndrome patient population: a cross-sectional assessment - David Huang; Eleni Jaswa; Chia-Ning Kao; Molly Quinn; Marcelle Cedars; Heather Huddleston (BMC, 2021)
Abstract Background Physical activity is a cornerstone for treatment of women with polycystic ovary syndrome (PCOS), but there are limited data on their exercise behaviors. A previous study identified PCOS patients of non-White ethnicity to be at higher risk for inadequate physical activity. Further data is needed to identify groups that would benefit from additional counseling in achieving adequate physical activity (APA). Therefore, this study examined correlates of APA within a multiethnic PCOS patient population. Methods Cross-sectional assessment of exercise behaviors within a multiethnic PCOS patient population was performed using the International Physical Activity Questionnaire (IPAQ). Kruskal-Wallis test was used to compare metabolic equivalents from physical activity among racial/ethnic groups. APA was defined as at least 150 min of moderate-intensity, or 75 min of vigorous-intensity, or an equivalent combination of moderate- and vigorous-intensity activity per week. Logistic regression analyses were performed to identify correlates of APA. Results Four hundred and sixty-five women of various racial/ethnic backgrounds were included in analysis: 62% (n = 287) self-identified as White, 15% (n = 71) as Hispanic, 11% (n = 52) as East/Southeast Asian, 7% (n = 32) as South Asian, and 5% (n = 23) as Black/African American. Significant differences were observed in metabolic equivalents (METs) from vigorous-intensity and total (moderate plus vigorous-intensity) exercise across racial/ethnic groups (p < 0.01); South Asian patients had the lowest metabolic expenditure in moderate-intensity, vigorous-intensity, and total exercise. Overall prevalence of APA was 66%; South Asian patients exhibited the lowest prevalence (46.9%). Ethnicity was a predictor for APA when controlled for age (p = 0.01); this finding was attenuated in logistic regression models that also controlled for age and body mass index (p = 0.05) as well as education level and parity (p = 0.16). Conclusions South Asian patients with PCOS exhibited the lowest metabolic expenditure and frequency of APA in our cohort. Differences in frequency of APA across racial/ethnic groups appear to be influenced by anthropometric and sociodemographic factors. Our findings present an opportunity for women's health providers to be cognizant and provide additional counseling regarding physical exercise to at-risk PCOS patients to improve their known higher risk for adverse long-term metabolic outcomes.